2005
DOI: 10.1161/circulationaha.105.541052
|View full text |Cite
|
Sign up to set email alerts
|

Techniques, Evaluation, and Consequences of Linear Block at the Left Atrial Roof in Paroxysmal Atrial Fibrillation

Abstract: Background-There are no reports describing the technique, electrophysiological evaluation, and clinical consequences of complete linear block at roofline joining the superior pulmonary veins (PVs) in patients with paroxysmal atrial fibrillation (AF). Methods and Results-Ninety patients with drug-refractory paroxysmal AF undergoing radiofrequency ablation were prospectively randomized into 2 ablation strategies: (1) PV isolation (nϭ45) or (2) PV isolation in combination with linear ablation joining the 2 superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
330
4
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 447 publications
(345 citation statements)
references
References 29 publications
2
330
4
9
Order By: Relevance
“…AF substrate also can be modified by the linear atrial ablation, which imitates the surgical MAZE procedure, in form of the roof line and, eventually, the inferior line on the LA posterior wall, connecting both superior and both inferior PVs. In this way, a complete electrical isolation of the whole LA posterior wall is achieved (so called "posterior box lesion"), as shown in Figure 3 [9,52]. Linear ablation of mitral isthmus between the mitral annulus and the left inferior PV can significantly modify AF substrate [53].…”
Section: Figure 2 Catheter Ablation Of Paroxysmal Af: Elimination Ofmentioning
confidence: 99%
“…AF substrate also can be modified by the linear atrial ablation, which imitates the surgical MAZE procedure, in form of the roof line and, eventually, the inferior line on the LA posterior wall, connecting both superior and both inferior PVs. In this way, a complete electrical isolation of the whole LA posterior wall is achieved (so called "posterior box lesion"), as shown in Figure 3 [9,52]. Linear ablation of mitral isthmus between the mitral annulus and the left inferior PV can significantly modify AF substrate [53].…”
Section: Figure 2 Catheter Ablation Of Paroxysmal Af: Elimination Ofmentioning
confidence: 99%
“…1,2,18) However, left mitral isthmus ablation, left atrial roof linear ablation, and linear catheter ablation to transect the anterior left atrium were shown to be necessary to maintain sinus rhythm particularly in patients with persistent AF. [19][20][21] Furthermore, in patients with persistent and permanent AF, circumferential PV ablation, combined with linear lesions in the right atrium in addition to left atrial and CS ablation, is reported to be feasible and safe, with a significantly high success rate. 22,23) However, creating transmural linear lesions with a multipolar ablation system or by the pull-back approach is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of adding an ablation line at the LA roof has been proven in several studies before. 16,17 Hocini and colleagues 17 reported that ablation along the LA roof resulted in a slowing of the AF process and termination of AF in 47% of patients who were diagnosed with PAF. In our study, in which complete transmurality and continuity were guaranteed by overlapping ablation and the addition of a CLAA ring, the modified endoscopic procedure had a similar success rate in PAF and non-PAF patients.…”
Section: Recurrence Of Atasmentioning
confidence: 99%